Aberrant gait biomechanics in individuals with ACL reconstruction are magnified during treadmill walking - Dewig, D. J.; Mills, H. R.; Evans-Pickett, A.; Pietosimone, B. G.; Blackburn, J. T. (Journal of Biomechanics, 2022)
Aberrant gait biomechanics following anterior cruciate ligament reconstruction (ACLR) likely contribute to post-traumatic osteoarthritis (PTOA) development. Gait biomechanics are typically assessed overground, but the use of instrumented/force-measuring treadmills is increasingly common. The purpose of this study was to compare gait biomechanics overground and on an instrumented treadmill in individuals with ACLR and healthy controls. Twenty-four individuals with ACLR and 24 healthy controls completed overground and gait biomechanics assessments. Biomechanical outcomes included peak vertical ground reaction force (vGRF), internal knee extension (KEM) and abduction (KAM) moments, and knee flexion (KFA) and adduction angles; KFA at heel strike; knee flexion displacement; and inter-limb symmetry for each outcome. Peak KEM (P < 0.001, 95%CI [-0.016, -0.007 xBW*Ht]) and vGRF (P < 0.001, 95%CI [-0.09. -0.03 xBW]) were significantly less symmetrical in the ACLR group compared to the control group on the treadmill but not overground. Additionally, peak KEM was smaller in the ACLR limb compared to the contralateral limb both overground (P = 0.005, 95%CI [-0.010, -0.001 xBW*Ht]) and on the treadmill (P < 0.001, 95%CI [-0.015, -0.007 xBW*Ht]), but this difference was 1.8x larger on the treadmill compared to overground. Peak KFA (P = 0.001, 95%CI [-4.2, -1.2°]) and vGRF (P < 0.001, 95%CI [-0.07, -0.03 xBW]) were smaller in the ACLR limb on the treadmill but not overground. These findings suggest aberrant gait biomechanics are exacerbated during treadmill walking post-ACLR and that evaluating kinematics and kinetics on instrumented treadmills may be valuable for assessing risk factors of PTOA development.